Stem anatomy of Pennisetum purpureum schum. (Poaceae) cultivars - de Brito, CJFA; Rodella, R. A.; Deschamps, F. C.; Alquini, Y. (Inst Tecnologia Parana, 1997)
Elephant-grass is known like a great feed to dairy and beef cattle al tropical regions. Its agricultural aspects have been very observed. However, its botanical, mainly anatomical characteristics are few studied. The objective of this work was to investigate the anatomical changes occurred in stems of three elephant-grass cultivars (ROXO, EMPASC 307 TESTO and EMPASC 309 AREIA) at three stages of plant development (4, 8 and 16 weeks after sprouting). The anatomical features were similar among cultivars. When stems were young (4 weeks), a disorganization of vascular bundles were detected. However, at 8 weeks stage the were organized as a definitive form. Was observed a magnified of lignification as the stems age, mainly caused by the increased of bundles sheaths that surrounds all vascular bundles.
Keywords: stem anatomy; Pennisetum purpureum; elephant-grass